Social Determinants of Anaemia among Pregnant Women in Rural Primary Health Settings: Evidence from a Gender-Sensitive Analysis - Kavitha V; Hilda Devi C (National Journal of Community Medicine, 2026)
Background: Anaemia during pregnancy is a major public health concern in India, especially in rural areas, where socio-demographic, nutritional, and gender-related factors increase vulnerability. The purpose was to assess the prevalence of anaemia among pregnant women in rural Coimbatore, examine its association with social and gender-related factors, and identify key predictors. Methods: A cross-sectional analytical study was conducted among 300 pregnant women attending antenatal clinics at rural PHCs in Coimbatore. Data on socio-demographics, diet, healthcare use, and gender factors (decision-making power, workload, food allocation) were collected using structured questionnaires. Haemoglobin was measured using Hemocue or Sahli’s method and classified per WHO. Associations were tested with Chi-square and multivariate logistic regression. Results: Anaemia prevalence was 68.3%, with moderate anaemia most common (35%). Higher prevalence occurred in adolescents (<20 years, 87.5%) and older women (≥40 years, 80%). Low education, housewife occupation, and low income were significant. Nutritional and healthcare risks included vegetarian diet, poor iron intake, irregular IFA, and <4 ANC visits. Independent gender predictors were limited decision-making (AOR=2.90), heavy workload (AOR=2.15), unequal food allocation (AOR=2.80), early marriage (AOR=1.85), and short birth spacing (AOR=2.40). Conclusion: Anaemia is highly prevalent, driven by socio-demographic, nutritional, and gender inequities. Integrated interventions addressing diet, ANC, and women’s empowerment are vital.